A Rare Case of Antepartum Spontaneous Septostomy in a Monochorionic Diamniotic Twin Pregnancy - Rati Chadha; Ian R. Lange; Lisa Bratz; Stephanie L. Cooper; Anne Roggensack; Jo-Ann Johnson (Hindawi Limited, 2012)
Spontaneous septostomy in a monochorionic diamniotic twin pregnancy is a rare phenomenon. We present a case of monochorionic diamniotic twin pregnancy with an intact dividing membrane seen in the 1st half of the pregnancy. At 26 weeks, when she was assessed for preterm contractions, the dividing membrane was not documented, which suggested spontaneous septostomy. There had been no invasive procedures during the pregnancy. She subsequently delivered at 29 weeks, secondary to preterm labor. No dividing membrane was noticed at the time of caesarian section. Spontaneous septostomy can complicate the management of monochorionic diamniotic twins by creating a pseudomonoamniotic environment resulting in cord entanglement, and difficulty in the diagnosis and management of twin-twin transfusion syndrome. We believe that such a case should be managed as monochorionic monoamniotic twin gestation.